Problem nieważności wyroku w świetle dekretu Roty Rzymskiej c. Salvatori z 22 marca 2013 r. - Góralski, Wojciech (Ius Matrimoniale, 2015)
The author presents and comments on a decree of the Roman Rota, which is an answer to to a complaint (made together with an appeal) of the respondent regarding annulment of a sentence nullitatis matrimonii case issued on 10 July 2009 by the tribunal of the first instance. This decree was appealed against due to presumed deprivation of the respondent of her right of defence as regards three procedural issues (given in the title). Having considered provisions of CIC and Dignitas connubii Instruction, the Rota judges decided that the respondent was not deprived of her right of defence in any of these issues, and, therefore, they decided that the annulment of the aforementioned decree was not proved.